1997
DOI: 10.1126/science.276.5319.1696
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Agonist of the Thrombopoietin Receptor as Potent as the Natural Cytokine

Abstract: Two families of small peptides that bind to the human thrombopoietin receptor and compete with the binding of the natural ligand thrombopoietin (TPO) were identified from recombinant peptide libraries. The sequences of these peptides were not found in the primary sequence of TPO. Screening libraries of variants of one of these families under affinity-selective conditions yielded a 14-amino acid peptide (Ile-Glu-Gly-Pro-Thr-Leu-Arg-Gln-Trp-Leu-Ala-Ala-Arg-Ala) with high affinity (dissociation constant approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
253
1
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(262 citation statements)
references
References 18 publications
3
253
1
3
Order By: Relevance
“…Cwirla et al (1997) reported that a type of dimer of AF12505, AF13948, had high activity, which was close to that of rhTPO.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Cwirla et al (1997) reported that a type of dimer of AF12505, AF13948, had high activity, which was close to that of rhTPO.…”
Section: Resultsmentioning
confidence: 69%
“…rhTPO had the highest activity. The peptide sequence of TPO-P is the same as that of AF12505, reported by Cwirla et al (1997). They reported that the activity of AF12505 was about 10 -4 times as high as that of rhTPO, calculated from the proliferative response of Ba/F3 hTPOR cells.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The library design was based on the linear sequence of AF12434 (ICS0 = 20 nM) where the 2B core sequence (GPTLRQWL) was fixed, and flanking parental residues were either deleted, substituted with alanine, or conserved. The oligonucleotides for this library were synthesized by an automated, codon-based, split and pool procedure [4]. As with the previous mutagenesis step, clones isolated from this library were ranked by their signal strength in the MBP ELISA, as shown in Figure 5.…”
Section: Familymentioning
confidence: 99%
“…[8,9] Obwohl die Inhibierung von Protein-Protein-Interaktionen (PPIs) mittels kleiner Moleküle lange Zeit als die ultimative Herausforderung in der Wirkstoffentwicklung galt, wurden nur sehr wenige Beispiele für solche PPI-Inhibitoren beschrieben. [10][11][12][13] Demgegenüber gibt es klare mechanistischkonzeptionelle Argumente dafür, dass PPI-Stabilisatoren großes Potential haben kçnnten. [14] LFA-1-Aktivatoren wären ein vielversprechender Ansatz für die Behandlung einer seltenen Erbkrankheit, bekannt als Leukozytenadhäsi-onsdeffizienz (LAD), oder als mçgliche Verstärker in der Tumorimmuntherapie.…”
unclassified